(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Systemic thinking can provide practice in multidisciplinary team working and improve organizational efficacy. This study aimed to determine the association between systemic thinking and working partnership in the employees of a medical sciences university in the south of Iran. Methods: A cross-sectional study was performed in Zahedan University of Medical Sciences (ZAUMS) in 2015. The study population consisted of all employees in ZAUMS; 370 participants were selected through stratified random sampling. Two standard questionnaires were used for data gathering. The data were analyzed in SPSS (v21) using Pearson, One way ANOVA and logistic regression. The level of significance was considered as 0.05. Results: In this study, 225 participants (60.8%) were female and the mean age of the participants was 34.7±8.7. The mean of working partnership for 362 participants was higher than the standard mean. Systemic thinking had a positive association with working partnership (p=0.001) and married status of the participants (p=0.04). Working partnership in male and older staff was more than others in ZAUMS (p<0.001 and 0.01, respectively). Conclusion: Systematic thinking had a positive association with the employees working partnership. Moreover, the male staff had better systematic thinking. It is recommended that the managers should promote systematic thinking in staff especially in females for better partnership and efficacy in organizations. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.233-237